Analysis of Financial Performance in Public Sector - Rida Perwita Sari; Hurip Tjahjono; Turino (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2018)
The study aims to examine the effect of Regional Original Income (PAD) on the financial performance of the Lamongan Regency (local government in East Java Province, Indonesia). The research was conducted in Lamongan using panel data 2010-2017 (eight years) to promote empirical facts. This study uses the Agency Theory and Fiscal Federalism Theory which are designed in the form of quantitative research approaches. The analysis technique in this study uses Structural Equation Modeling (SEM) with a variance based or component-based approach with Partial Least Square (PLS). The results of this study are the Regional Original Revenue (PAD) effect on three components of regional financial performance as measured by the degree of decentralization, regional financial dependency ratio, and local financial independence ratio. These results indicate that that financial performance of local government is influenced by the PAD. The average value of 20% government of Lamongan can maintain and improve the success achieved and have been effective in doing excavation source - a source of local revenue.